If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + -6)(x + -6) + 10 = 0 Reorder the terms: (-6 + x)(x + -6) + 10 = 0 Reorder the terms: (-6 + x)(-6 + x) + 10 = 0 Multiply (-6 + x) * (-6 + x) (-6(-6 + x) + x(-6 + x)) + 10 = 0 ((-6 * -6 + x * -6) + x(-6 + x)) + 10 = 0 ((36 + -6x) + x(-6 + x)) + 10 = 0 (36 + -6x + (-6 * x + x * x)) + 10 = 0 (36 + -6x + (-6x + x2)) + 10 = 0 Combine like terms: -6x + -6x = -12x (36 + -12x + x2) + 10 = 0 Reorder the terms: 36 + 10 + -12x + x2 = 0 Combine like terms: 36 + 10 = 46 46 + -12x + x2 = 0 Solving 46 + -12x + x2 = 0 Solving for variable 'x'. Begin completing the square. Move the constant term to the right: Add '-46' to each side of the equation. 46 + -12x + -46 + x2 = 0 + -46 Reorder the terms: 46 + -46 + -12x + x2 = 0 + -46 Combine like terms: 46 + -46 = 0 0 + -12x + x2 = 0 + -46 -12x + x2 = 0 + -46 Combine like terms: 0 + -46 = -46 -12x + x2 = -46 The x term is -12x. Take half its coefficient (-6). Square it (36) and add it to both sides. Add '36' to each side of the equation. -12x + 36 + x2 = -46 + 36 Reorder the terms: 36 + -12x + x2 = -46 + 36 Combine like terms: -46 + 36 = -10 36 + -12x + x2 = -10 Factor a perfect square on the left side: (x + -6)(x + -6) = -10 Can't calculate square root of the right side. The solution to this equation could not be determined.
| x-2*y+3=0 | | X^2-13x=-12 | | 8-2m=1/2m+3 | | 5p^2+3=1 | | 4y=-7(x+4) | | 4x-(6x-2y)+(2x-7y)= | | =9(w+2)+3(w-5) | | -3.4r=30.94 | | 4x-(6x-27)+(2x-7y)= | | =3(2m+4)+2(6-3m) | | 7x+5=8x+10 | | (2m+4)(2)= | | 30+18+x*4=100 | | 30+15+x*4=100 | | 32x+72=90-51x | | 30+12+x*4=100 | | (a+bi)(a-bi)-4i(a-bi)=4-8i | | 4x-8=16+8x | | 20-(4x+2y)= | | z*z-4i*z=4-8i | | 3z=5*1.2 | | -x^2+3=(4x-1) | | 2y+6.4=10+4y | | -5x+3(x+4)=8 | | 5x^2-48x-720=0 | | (x-2+i)(x-2-i)=equation | | 31-x-12=15 | | 112+7x= | | -4m^2-8m+1=5 | | 2(3x-6)=16 | | x+20+10x=10+9x | | B(x)=45.50-0.10x |